DIFFERENT ROUTES FOR THE SYNTHESIS OF BENZALDEHYDE-BASED DIHYDROPYIMIDINONES VIA BIGINELLI REACTION - Ilfahmi, Yan Alamanda; Fadlan, Arif (Jurnal Kimia Riset, 2023)
Multicomponent reactions involving three or more reactants are commonly used to prepare dihydropyrimidinone with various bioactivities. This study reports the different routes for the synthesis of benzaldehyde-based dihydropyrimidinone via the Biginelli reaction and investigates the yield of the obtained products. The synthesis was performed via routes A, B, C, D, and E based on the formation of iminium, enamine, and Knoevenagel intermediates between urea, benzaldehyde, and ethyl acetoacetate. Route A, through a one-pot reaction via iminium, produced dihydropyrimidinone with a yield of 58%. The product from route B via iminium was obtained in 62% yield. Route C and D occurred via enamine at room temperature, and reflux gave the product 31% and 40% yield, respectively. Route E involving Knoevenagel intermediate provided the product in a 38% yield. 1H NMR, FTIR, and MS spectroscopic techniques were used for structure elucidation.